Antennas and propagation for body-centric wireless communications - Hall, Peter S.; Hao, Yang (Artech House antennas and propagation library., 2012)
Theory, design, and applications of wireless antennas for on-body electronic systems are covered in this updated edition. Advances in physical phantom design and production, recent developments in simulation methods and numerical phantoms, descriptions of methods for simulation of moving bodies, and the use of the body as a transmission channel are discussed as well as applications like Bluetooth headsets together with detailed treatment of techniques, tools, and challenges in developing on-body antennas for an array of medical, emergency response, law enforcement, personal entertainment, and military applications. Topics include: energy propagation around and into the body; on-body communication channels at microwave frequency bands, low frequency bands and ultra wideband systems for WPANs and WBANs; body-centric UWB antennas and channels; wearable mobile, EBG, and "smart fabric" antennas for cellular and WLAN communications; and telemedicine. --